Evaluation of chemical management against Fusarium oxysporum f. sp. ciceri isolated from local fields of Saikheda region, M.P using some fungicide formulations - Dixit, Shubhank; Dhok, Pushpanjali; Rajoriya, Ashutosh; Kadu, Dhruv (Indian Journal of Plant Protection, 2025)
This study aimed to assess the effectiveness of five system g ic and six contact fungicides in vitro for managing Fusarium oxysporum f.sp.ciceri (Foc), a significant pathogen causing Fusarium wilt in chickpeas (Cicer arietinum L.). Using a dual culture technique, the antagonistic capabilities of these fungicides against Foc were investigated. Systemic fungicides tested included Propiconazole (Tilt), Carbendazim (Bavistin),Kresoxim-methyl + Hexaconazole (Tata ayaan), Hexaconazole (Contaf plus), and Tubeconazole + Sulphur (unspecified), while contact fungicides comprised Zineb (Indofil Z-78), Propineb (Sanipeb), Chlorothalonil (Kavach), Captan (Agrox), Mancozeb (Sparsh), and Copper oxychloride (Bensaan). The inhibition of Foc mycelial growth was evaluated following incubation in a BOD incubator at 25± 2°C for 7 days. Resultsdisplayed varied efficacy among the tested fungicides, providing insights into their potential for fusarium wilt management in chickpeas. This research contributes to the development of effective strategies for mitigating economic losses associated with Fusarium wilt in chickpea cultivation.